2015
DOI: 10.3389/fmech.2015.00002
|View full text |Cite
|
Sign up to set email alerts
|

Additive Manufacturing of Co-Cr-Mo Alloy: Influence of Heat Treatment on Microstructure, Tribological, and Electrochemical Properties

Abstract: Co-Cr-Mo alloy samples, fabricated using Laser Engineered Net Shaping-a laser-based additive manufacturing technology, have been subjected to heat treatment to study its influence on microstructure, wear, and corrosion properties. Following L9 Orthogonal array of Taguchi method, the samples were solutionized at 1200°C for 30, 45, and 60 min followed by water quenching. Aging treatment was done at 815 and 830°C for 2, 4, and 6 h. Heat treated samples were evaluated for their microstructure, hardness, wear resis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(31 citation statements)
references
References 16 publications
1
30
0
Order By: Relevance
“…Peaks obtained from diffractometric studies with a very similar value of the 2h angle, define as a cobalt solution with Miller indexes (101), which unequivocally suggests the presence of the a solution. 39 The DTA Results…”
Section: Microstructural Analyses Of Castingsmentioning
confidence: 99%
“…Peaks obtained from diffractometric studies with a very similar value of the 2h angle, define as a cobalt solution with Miller indexes (101), which unequivocally suggests the presence of the a solution. 39 The DTA Results…”
Section: Microstructural Analyses Of Castingsmentioning
confidence: 99%
“…Such internal residual stress could generate high strain and thereby affects the accuracy [36,37]. One solution to circumvent this problem is the employment of heat treatment after printing the metal that could at the same time change the micro-structure [34,38].…”
Section: Mechanical Properties Of 3d Printed Metalsmentioning
confidence: 99%
“…However, in general, lower the I corr and nobler the E corr better will be the corrosion resistance of a material. Therefore, to identify the surface for best corrosion performance Gray relational grade analysis, 29,30 which combine multiple responses into a single index, was performed using I corr and E corr data of LSM samples only. The analysis showed that the corrosion performance of LSM samples processed at 5 mm/s will be best among the samples in polished condition.…”
Section: Corrosion Performancementioning
confidence: 99%